Proceedings of the 13th International Conference on Ubiquitous Information Management and Communication (IMCOM) 2019 - Lee, Sukhan; Ismail, Roslan; Choo, Hyunseung (Advances in Intelligent Systems and Computing,, 2019)
Over past few years, technologies have experienced boundaries getting blurred and concept of convergence to gain prominence. Harnessing from this, two main tracks for information processing management and communication are held, covering both research and application works of information management, intelligent information processing, interaction management, networking/ telecommunications, and social interaction. This book creates unique opportunity for research convergence among truly diverse technology domains of computer science. Leveraging from this diversity of topics, researchers get to generate novel research ideas by seeking application of their research in a different technology domain. This volume represents the collection of papers presented at the 13th International Conference on Ubiquitous Information Management and Communication (IMCOM 2019), held on 4-6 January 2019 in Phuket, Thailand. Out of 228 papers submitted from all around the world 88 papers were accepted for presentations. The 88 contributions to this volume are organized into 5 chapters: Chapter 1. Network Evolution, Chapter 2. Intelligent and Secure Network, Chapter 3. Image and Video Processing, Chapter 4. Information Technology and Society, and Chapter 5. Data Mining and Learning. Our editors wish readers to find this volume informative and enjoyable.